Measuring Factors Affecting Dividend Policy and Value In Non-Cyclical Consumer Companies - I Gede Cahyadi Putra; Ida Ayu Ratih Manuari; Ni Made Adelia Andika Putri (Jurnal Ilmiah Akuntansi, 2023)
Economic growth in non-cyclical consumer industries in 2015–2018 tended to increase, however in 2020 there was a sharp decline in Indonesia's economic growth due to Indonesia being hit by the Covid-19 pandemic so it is deemed necessary to pay close attention to the prospects of non-cyclical consumer companies as measured by company value because company value is a reflection of company performance. The purpose of this research is to analyze and prove empirically that profitability, managerial ownership, leverage affect dividend policy and corporate value of consumer non-cyclicals. This study used a purposive sampling technique with several criteria in order to obtain 8 samples of consumer non-cyclicals companies and the analysis technique used was PLS (Partial Least Square). This study found that the higher the profitability and leverage a company has, the higher its dividend distribution policy will be. Likewise, the higher the profitability, ownership and leverage a company has, the higher the firm value the company has. The implications of this research are expected to be the foundation and information for investors in optimizing investment decisions by identifying the factors that influence firm value.